Studies on eco-farmer-friendly practices for management of soft rot of ginger (Zingiber officinale) - and NEHA AHLUWALIA, N. P. DOHROO*, SANDEEP KANSAL (Indian Phytopathology, 2015)
An experiment was conducted to evaluate the efficacy of integrated module of chemicals and non-chemicals against soft rot disease in ginger (Zingiber officinale Rosc.) at Dr Y.S. Parmar University of Horticulture and Forestry, Nauni, during 2011-12 and 2012-13. The in vitro study on mycelial growth inhibition of Pythium aphanidermatum revealed that among different antagonists evaluated Trichoderma harzianum proved most potent bioagent in limiting growth of the pathogen of soft rot of ginger. The two years field study indicated that rhizome treatment in hot water at 47Â°C for 30 min and soil application of T. harzianum @ 2.5 kg/ 50 kg FYM/ha, followed by three drenching of Mancozeb @ 0.25% was most effective in limiting the incidence of soft rot on ginger besides having their significant response in improving the growth and yield.